100% citrus juice: Nutritional contribution, dietary benefits, and association with anthropometric measures. Issue 1 (2nd January 2017) - Rampersaud, Gail C.; Valim, M. Filomena
ABSTRACT: Citrus juices such as 100% orange (OJ) and grapefruit juice (GJ) are commonly consumed throughout the world. This review examines the contributions of OJ and GJ to nutrient intake, diet quality, and fruit intake, and supports citrus juices as nutrient-dense beverages. This review also explores the research examining associations between OJ and GJ intake and anthropometric measures. Citrus juices are excellent sources of vitamin C and contribute other key nutrients such as potassium, folate, magnesium, and vitamin A. OJ intake has been associated with better diet quality in children and adults. OJ intake has not been associated with adverse effects on weight or other body measures in observational studies in children and adults. In adults, some observational studies report more favorable body mass index or body measure parameters in OJ consumers compared to nonconsumers. Intervention studies in adults report no negative impacts of OJ or GJ consumption on anthropometric measures, although these measures were typically not the primary outcomes examined in the studies. Moderate consumption of citrus juices may provide meaningful nutritional and dietary benefits and do not appear to negatively impact body weight, body composition, or other anthropometric measures in children and adults.